Tailoring IGZO composition for enhanced fully solution-based thin film transistors - Moreira, Marco (2020)
UID/CTM/50025/2019 H2020 NMP-22-2015 project 1D-NEON Grant Agreement 685758 SFRH/BD/116047/2016 IDS-FunMat-INNO project FPA2016/EIT/EIT Raw Materials Grant Agreement 15015